Litho-structural framework of mineralization along the Ait Atmane fault zone (High Atlas, Morocco): Insights from remote sensing and field data - Ijaajaane Abdelhak; Ait Ali Abdelkhiar; Kajji Souhaila; Si Mhamdi Hicham; Baidder Lahssen; Raji Mohammed (E3S Web of Conferences)
Geological mapping through remote sensing is an essential method for georesource exploration. This study focuses on mapping structural lineaments in the Ait Atmane region, located at the limite between the Central High Atlas and Eastern High Atlas sub-domains. The area is characterized by a Meso-Cenozoic sedimentary cover. The primary objective is to analyze the distribution of fractures associated with the Ait Atmane fault and their relationship with Pb-Zn±Fe mineralized structures, aiming to identify metallotects for mining exploration. To achieve this, Sentinel-2A and ASTER images and ASTER GDM data were utilized to extract structural lineaments. After correcting the images, data processing centered on the automated detection and extraction of structural lineaments. Validation of the results was carried out through comparison with Google Earth imagery, existing geological maps and field observations. The findings show four predominant fractures systems: NW-SE, NE-SW, and ENE-WSW, affecting Jurassic and Cretaceous formations along the Ait Atmane fault. The Pb+ Zn ± Fe mineralization occurs in veins hosted in Pliensbachian reef limestone formations and is carried by faults trending ENE-WSW and ESE-WNW with a subvertical dip. This research highlights the critical role of structural controls in the localization and distribution of mineral resources along the Ait Atmane Fault Zone.